Annie Ernaux à l’international - Élise Hugueny-Léger (Contextes)
Annie Ernaux’s works have often been called universal, in spite of depicting personal experiences steeped in the precise historical and geographical context that is post-war France. The fact that her work is widely disseminated internationally, in French and in translation, and that she was awarded the globally acclaimed Nobel Prize in literature, confirms the broad reach of her writing and the themes she tackles, including women’s place in society and social mobility. This article adopts a transnational perspective to evaluate the circulation and reception of her works, by shedding light on the aftermath of the Nobel Prize and on the pertinence of the notion of “transfuge” (class defector of class migrant) internationally. Finally, it considers Ernaux’s writing as being able to generate other works and discourse beyond the French context.